Simulation Based Mastery Learning of Transesophageal Echocardiography - Koenig, Peter; Patel, Shivani; Cohen, Elaine R.; Hauck, Amanda; Husain, Nazia; McGaghie, William C. (Pediatric cardiology, 2023)
Transesophageal echocardiography (TEE) education is part of pediatric cardiology fellow training. Simulation-based mastery learning (SBML) is an efficient and valuable education experience. The aim of this project was to equip trainees with the basic knowledge and skill required to perform a pediatric TEE. The secondary aim was to assess the utility of using SBML for pediatric TEE training. The target group is trainees from pediatric cardiology and cardiac anesthesia who participated in a TEE bootcamp. A baseline knowledge pretest was obtained. The knowledge session consisted of preparation via reading material, viewing recorded lectures and completing an iterative multiple-choice examination, which was repeated until a minimum passing score of 90% was achieved. The skills session involved a review of TEE probe manipulation and image acquisition, followed by rapid cycle deliberate practice using simulation to acquire TEE skills at 3 levels, advancing in complexity from level 1 to level 3. Eight individuals (7 pediatric cardiology fellows at varying training levels and one anesthesia attending) participated in the TEE bootcamp. All reached a minimum knowledge post test score of at least 90% before the skills session. All subjects reached mastery in TEE probe manipulation. All reached mastery in image acquisition for the skill level that they attempted (level 1—8/8, level 2—8/8, level 3—4/4, with 4 participants not attempting level 3). A TEE bootcamp using SBML is a powerful medical education strategy. SBML is a rigorous approach that can be used to achieve high and uniform TEE learning outcomes among trainees of different training levels and backgrounds.